DETEKSI DAN PREVALENSI TELUR CACING NEMATODA PADA BABI DOMESTIK (SUS SCROFA DOMESTICUS) DI DESA JAGARAGA KECAMATAN KURIPAN KABUPATEN LOMBOK BARAT - Ni Luh Lasmi Purwanti; Nofisulastri Nofisulastri; Muhammad Munawaroh; Candra Dwi Atma; I Gede Bagas Upaditha Adresya Kaler; Erprinanda Galuh Berliana (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2026)
Pigs can transmit zoonotic gastrointestinal parasitic diseases originating from protozoa and helminths to humans. Gastrointestinal nematodes in pigs are one of the factors that can impair animal health and reduce productivity. This study aimed to detect and determine the prevalence of nematode eggs in domestic pigs (Sus scrofa domesticus) in Jagaraga Village, Kuripan District, West Lombok. A total of 30 fresh fecal samples were collected randomly and examined using native and flotation methods. Nematodes were identified microscopically based on egg morphology. Three nematode species were detected, namely Ascaris suum (30%), Oesophagostomum dentatum (26.66%), and Trichuris suis (16.66%). The highest prevalence was observed in Ascaris suum. These findings indicate the presence of nematode infections in the study area, which may affect livestock productivity and pose a zoonotic risk. Therefore, improvement of pen sanitation, implementation of routine deworming programs, and regular surveillance are necessary to control gastrointestinal nematode infections.